Arylthio-substituierte Nitrilylide aus der Thermolyse von 4-Arylthio-3-oxazolin-5-onen - Peter Wipf; Heinz Heimgartner (CHIMIA)
Thermolysis of 4-arylthio- and 4-benzylthio-3-oxazolin-5-ones leads to arylthio- and benzylthio-substituted nitrile ylides, which undergo 1,3-dipolar cycloadditions with reactive dipolarophiles to give 5-membered aza-heterocycles (Schemes 1 and 2). In the absence of reactive dipolarophiles, the nitrile ylides isomerize to 2-aza-butadienes, which can be trapped by ethyl propiolate to yield pyridine derivatives (Scheme 3).